Empowering Cadres to Increase Parental Awareness of Tuberculosis (TB) in children Prevention in Pacarkembang District, Surabaya - indriatie, indriatie; Novitasari, Aida; Nur Hasanah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
ABSTRACT. The working area of Pacarkeling Health Center includes Pacarkeling and Pacarkembang villages, Surabaya. The development of health promotion activities at the health center largely involves active community participation through health cadres. Tuberculosis (TB) in children cases in Surabaya remain high, influenced by behavioral and environmental factors. TB is not limited to adults but also affects children, thus requiring comprehensive understanding of the disease, its signs and symptoms, treatment, and prevention. The objectives of this community service program are to assess the understanding of cadres regarding Tuberculosis (TB) in children, assess their knowledge of Tuberculosis (TB) in children prevention; and evaluate their awareness and involvement in counseling and educational activities related to Tuberculosis (TB) in children prevention. The targets and outcomes of the community service program were successfully achieved. The mandatory output for the PKM (Community Service Program) scheme included an increase in cadres’ understanding of Tuberculosis (TB) in children and its prevention at the